2021
DOI: 10.31014/aior.1993.04.02.202
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Intelligence: A Strengthening in Efforts to Improve Student Learning Achievement

Abstract: The purpose of this study was to determine the relationship between interpersonal intelligence and student learning outcomes so that there is an increase and strengthening of student achievement. The method used in this research is field research with a correlational quantitative approach which aims to analyze the relationship between interpersonal intelligence and student achievement. The results of this study found that there is a significant relationship between interpersonal intelligence and student achiev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…Thus, it is concluded that t count > t Table is equal to 2.842 > 1.98027, then Ho rejected, which means interpersonal intelligence positively influences learning achievement. The results of these calculations follow research conducted by Istapra et al (2021) because the relationship of interpersonal intelligence of a student has a great influence on the performance of the student's achievements. The results showed that students an average interpersonal intelligence in this study are in the category of" medium " by 70%.…”
Section: Interpersonal Intelligence On Learning Achievementsupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, it is concluded that t count > t Table is equal to 2.842 > 1.98027, then Ho rejected, which means interpersonal intelligence positively influences learning achievement. The results of these calculations follow research conducted by Istapra et al (2021) because the relationship of interpersonal intelligence of a student has a great influence on the performance of the student's achievements. The results showed that students an average interpersonal intelligence in this study are in the category of" medium " by 70%.…”
Section: Interpersonal Intelligence On Learning Achievementsupporting
confidence: 69%
“…Evaluation of a student's learning outcomes to determine learning goals is known as learning achievement (Walid & Hadiwinarto, 2021). Through learning outcomes, students can experience learning progress (Istapra et al, 2021). It is concluded that learning achievement is the result of the learning process that each student does for effort and hard work to achieve a learning goal.…”
Section: Literature Reviewmentioning
confidence: 99%